Social Workers Response to Covid-19 Pandemic: Learning’s, Opportunities and Challenges - Maske, Sudhir; Dey, Rituparna (International Journal of Psychosocial Rehabilitation, 2020)
COVID- 19 pandemic posed many challenges to human existence. It accounted its first instance in India on January 30, 2020. The Indian Government then on took a prudent stride of declaring the lockdown which halted everything in the nation. As other human service professionals were dealing with people those who were in need and crisis. It was equally assumed and expected that the social work professionals should also respond to challenges efficiently and effectively while fostering the values of acceptance and service towards needy. It has been observed that social work practitioners were also facing the brunt challenges in carrying out their duties towards the society during pandemic. This article is an outcome of study which was conducted to understand and explore the issues and challenges faced by the social work practioners in diverse settings. The social work researcher had conducted in-depth interviews of social work practitioners which include both males and females. The nature of study was qualitative and captured the first-hand narratives from the practitioners through in-depth interviews. The researcher has found that the social worker professionals.